Model Pemberdayaan Ekonomi Petani Berbasis Pengembangan Industri Hulu ke Hilir untuk Meningkatkan Nilai Tambah Potensi Desa - Zahida I’tisoma Billah; Sri Mulyani (Fakultas Ekonomi dan Bisnis Islam, 2019)
In Indonesia, technology development in the agribusiness sector needs to be improved, because the majority of Indonesia’s population works in the agricultural sector. The problem faced by farmers today is a lack of information related to the management of the agricultural products industry. They only take care of the fields and irrigate, and fertilize until harvest and then sell it in the form of grain. Even though the big advantage that farmers get is when managing the grain into rice. Likewise, the provision of agricultural facilities or tools for postharvest activities, is of particular concern from the local government. For this reason, a method is needed so that their agricultural products can be valued on the market. This study uses a qualitative method with a descriptive approach through case studies on assisted farmer groups in Sumberejo Purwosari Village, Pasuruan Regency. Data collection techniques are obtained through observation and interviews where sampling in interviews uses purposive sampling techniques, while the data analysis technique is done by reducing data, presenting data and drawing conclusions. The economic empowerment of farmers is provided regarding counseling and training on agricultural product management, assistance to selling products to the market. The potential of natural resources in Sumberejo village is very varied, such as durian, brown rice, coffee beans which are later processed into ground coffee, and cassava which will be processed into cassava chips which are processed by the village farmers’ mothers. The results showed that the village self-reliance program consisted of: a. Prosperity of farm families, where each farmer family is encouraged to have plants in their yard, at least to fulfill kitchen needs, b.) Increase production by processing SDA equipped with skills and knowledge about procedures for making to marketing, c.) Meeting capital requirements by establishing savings and loan cooperatives for members of farmer groups. The development of agricultural products from upstream to downstream makes farmers able to enjoy the fruits of their labor without selling their produce to middlemen who often play with prices to small farmers.